KATHMANDU TEACHER’S VIEW OF THE USE OF TECHNOLOGY IN AN ENGLISH LESSON - CAN, Mustafa Harun; Batsa, Braza Kishore (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2018)
This paper studied teachers’ view and practices of technologies in teaching English in public schools in Kathmandu, the capital city of Nepal. It collected teachers’ views and the problems they encountered in using technology in the English language. It targeted to find out what sorts of technologies they used in the classroom. The result revealed that the mostly implemented technological means were cassette player, cell phone, computer, television, video recorder, and email. A questionnaire was prepared by the research holder and applied to 50 teachers of the secondary level to gather data. The research found that most of the teachers considered the use of technology as important tools to foster teaching and learning. The research concluded that lack of appropriate class time, accessibility of the relevant technologies and sufficient training was the main hurdles in the process of use of technology.